Multifunctional Polypropylene Core for Aerospace Sandwich Composite Panels. (2016) - Riccio, A.; Raimondo, A.; Sellitto, A.; Acanfora, V.; Zarrelli, M.
Abstract: The sandwich composite panels, due to their highly specific mechanical properties, are widely used in many engineering fields (such as the aeronautical, railways and automotive). In this work, a numerical study is presented on the impact behavior of several sandwich composite panels configurations with polypropylene core, usually adopted for aerospace applications, with the aim to assess their mechanical properties and to make a selection of the best configurations taking into account their multifunctional characteristics. The existing limits in current aeronautical sandwich panels have been assessed and techniques/solutions able to improve (even through the utilization of micro and nano fillers) the multifunctional and structural properties have been explored. Indeed, resistance to fire and resistance to impact events have been selected as the main characteristics of interest for the presented study. Low-speed impact tests (according to the ASTM standards) on sandwich composite panels with polypropylene core have been simulated by means of the commercial FEM software "Abaqus". Low velocity impacts can switch complex damage mechanisms (such as delaminations or large indentations) in composite panels. These damage mechanisms are of major concern from a structural point of view because they can suddenly reduce the loading carrying capability without being visible in programmed visual inspections. As a result of the performed simulations, the low velocity impact induced damage, in terms of delamination and indentation, has been evaluated for several sandwich panels with varying polypropylene core material composition. The outputs have been compared providing a first estimation of the capability to resist to impact event provided by several polypropylene core configurations. The resistance to impact events have been associated to the fire resistance capability of the analyzed material core configurations proving a comprehensive insight on the multifunctional behavior of sandwich composite panels with polypropylene core.